DENTAL MANAGEMENT OF PATIENTS WITH PARKINSON’S DISEASE - DR. M.P.SANTHOSH KUMAR M.D.S. (International Journal of Pharma and Bio Sciences, 2015)
Parkinson’s disease is a progressive disorder of the nervous system that affects the motor function. However, the pathogenesis of this disease is complex and involves many molecular, cellular and physiological pathologies. Parkinson’s disease can affect the mouth and subsequently oral health is affected. The clinical features, pathophysiology, medical management, dental findings and management of patients with parkinon’s disease in dental office has been discussed in this review article.